Systems with Hidden Attractors From Theory to Realization in Circuits - Pham, Viet-Thanh; Volos, Christos; Kapitaniak, Tomasz (SpringerBriefs in Nonlinear Circuits,, 2017)
This brief provides a general overview of nonlinear systems that exhibit hidden-attractor behavior, a topic of interest in subjects as divers as physics, mechanics, electronics and secure communications. The brief is intended for readers who want to understand the concepts of the hidden attractor and hidden-attractor systems and to implement such systems experimentally using common electronic components. Emergent topics in circuit implementation of systems with hidden attractors are included. The brief serves as an up-to-date reference on an important research topic for undergraduate/graduate students, laboratory researchers and lecturers in various areas of engineering and physics.